Readings in Unemployment / Studies in Unemployment. Prepared for the Special Committee on Unemployment Problems, United States Senate, 86th Congress. - Dion, Gérard (Relations industrielles / Industrial Relations, 1960)
The article reviews the books, "Readings in Unemployment," prepared for the Special Committee on Unemployment Problems, United States Senate, 86th Congress, 1st Session (1716 pp.) / and "Studies in Unemployment," prepared for the Special Committee on Unemployment Problems, United States Senate, 86th Congress (432 pp.).